A Review of Vocabulary Research in English Textbooks Based on Corpora - Li, Shuxian (International Journal of Humanities and Education Development (IJHED), 2024)
With the promulgation of high school New Curriculum Standards, various new textbooks have emerged, and the presentation of knowledge content for vocabulary that has a profound impact on English learning in these textbooks has also changed. Corpus linguistics often uses corpus software as a research tool to efficiently search and extract language patterns from numerous language examples. The research process is objective and the results are scientific. Therefore, more and more scholars are using corpus tools to study vocabulary in English textbooks. This study will summarize the current status of vocabulary research in English textbooks based on corpus and look forward to the development trends in this field. The study aims at revealing the distribution and development patterns of vocabulary in various English textbooks, provide inspiration for future textbook compilation, and provide reference for future vocabulary evaluation research in English textbooks.